The Tradition of Surrendering Penne Anreang in a Bugis Suppa Marriage - Muchsin, Agus; Anwar, Wirani Aisiyah (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
Penne anreang is a hereditary tradition that is carried out during weddings, the Suppa community assumes that the penne anreang tradition is a social aspect because it is seen as something important and has high traditional values. The impact if this tradition is not carried out will have an impact on social sanctions in the community itself, such as ridicule and gossip from neighbors and people in the area. This study aims to analyze the tradition of submission of penne anreang which is reviewed in Islamic law. The results show that this tradition looks so simple but from its simplicity, many messages will be conveyed, for example, people are required to respect and respect each other. Knowing the rights and obligations as husband and wife, how to deal with problems both in domestic life, the realization of the wife’s responsibility in navigating the household ark, being able to serve her husband both physically and mentally, as well as in society. Seeing from the meaning implied in the submission of penne anreang, it can be concluded that this tradition is still carried out and does not conflict with the teachings of Islam because every meaning that will be conveyed all leads to goodness